The Phenomenon of Celebrity Recruitment as Legislative Members from the Perspective of Dramaturgy Theory - Maddi, Jaenal Hasyim; Purnomo, Marlinda Irwanti (Eastasouth Institute, 2025)
The phenomenon of recruiting celebrities as legislative members has become a trend in various countries, including Indonesia. This phenomenon has sparked debates, particularly concerning the capabilities, credibility, and motivations of celebrities in politics. This theory likens social life to a stage performance, where individuals play specific roles to gain social recognition. This study employs a qualitative research method with a case study approach on several celebrities who have become legislative members. The findings indicate that many celebrities utilize their popularity as social capital to gain voter support but often face challenges in adapting to the complex legislative role. The study also reveals that the performance displayed in public often differs from the reality behind the scenes. In conclusion, the image-building strategies employed by celebrity politicians significantly determine their success in establishing political legitimacy in the eyes of the public.